Securing AI/ML Pipelines in the State Government Sector: Threat Models, Controls, and Governance - Swapan Arora (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Government authorities and public sector organizations increasingly deploy artificial intelligence andmachine learning systems in critical services including benefits eligibility verification, fraud detection,visitor flow optimization, and health monitoring. However, existing cybersecurity frameworks inadequately address vulnerabilities inherent in machine learning